Factors influencing the length of stay in forensic psychiatric settings: a systematic review - Aikaterini Dima; Adonis Wazir; Raquel Clark-Castillo; Iordanis Zakopoulos; Shubulade Smith; Fiona Gaughran (BMC, 2024)
Abstract Background Forensic psychiatry is often associated with long admissions and has a high cost of care. There is little known about factors influencing length of stay (LOS), and no previous systematic review has synthesised the available data. This paper aims to identify factors influencing the LOS in forensic psychiatry hospitals to inform care and interventions that may reduce the length of admissions. Methodology A systematic review was conducted by searching major databases, including PubMed, EMBASE and PsycInfo, from inception until May 2022. Observational studies conducted in forensic hospitals that examined associations between variables of interest and LOS were included. Following data extraction, the Newcastle‒Ottawa Scale was used for quality appraisal. No meta-analysis was conducted due to heterogeneity of information; a quantitative measure to assess the strength of evidence was developed and reported. Results A total of 28 studies met the inclusion criteria out of 1606 citations. A detailed quantitative synthesis was performed using robust criteria. Having committed homicide/attempted homicide, a criminal legal status with restrictions, and a diagnosis of schizophrenia-spectrum disorders were all associated with longer LOS. Higher Global Assessment of Functioning (GAF) scores were associated with a shorter LOS. Conclusion High-quality research examining factors associated with LOS in forensic psychiatry is lacking, and studies are heterogeneous. No modifiable characteristics were identified, and thus, practice recommendations were not made. There is an increasing necessity to understand the factors associated with longer admissions to inform care and increase success in reintegration and rehabilitation. This paper provides recommendations for future research.